VD_FINDINFO Réc-civile / 2011 / 19 vom 3. Oktober 2011 - VD Tribunal cantonal (2011)
RÉCUSATION, COMPÉTENCE RATIONE MATERIAE, CONDITION DE RECEVABILITÉ | 6 al. 1 let. a ROTC, 132 CPC (CH), 47 CPC (CH), 50 al. 1 CPC (CH), 50 al. 2 CPC (CH), 59 al. 2 let. a CPC (CH), 8a al. 5 CDPJ